Hematologic changes induced by erythropoietin versus intermittent normobaric hypoxia - F. Sanchis-Gomar; V. E. Martinez-Bello; D. A. Martinez-Bello; A. L. Nascimento; R. García-Vallés; T. Brioche; B. Ferrando; S. Ibáñez-Sania; H. Pareja-Galeano; M.C. Gómez-Cabrera; J. Viña (Asociación Española de Ciencias del Deporte, 2010)
Recent publications reflect the anti-doping authorities' concern about the use of altitude simulator systems, since these technologies could be considered as doping methods. The major aim of our study was to compare the effect of two different rHuEpo treatments with a normobaric intermittent hypoxic (NIH) protocol regarding the modifications of hemoglobin, hematocrit and reticulocytes values in an animal model. Although these hematological parameters are of secondary nature, some international sport federations currently exclude athletes, who show aberrant values of these parameters, from competition. Twenty-four young male Wistar rats (3 months and ~300g weight) were randomly divided in 3 experimental groups: normobaric intermittent hypoxic group  (12h pO2 12% /12h pO2 21%) (n=8); the group treated with 300 UI of rHuEpo (n=8) and the group treated with 500 UI of rHuEpo (n=8).The rHuEpo was administered subcutaneously 3 times/week. All the treatments lasted 15 days. Two blood samples were obtained in every experimental group. The first one before the treatments and the second one 15 days after the treatments. Our results show similar and statistically significant increments in the hemoglobin, hematocrit and reticulocytes values after 15 days of treatment with 300 UI of rHuEpo or NIH. The treatment with 500 UI of rHuEpo induced a higher increase in the hematological parameters determined in our study when compared with the other treatments (NIH and rHuEpo 300 UI). The main conclusion of our study is that the hematological modifications achieved with a NIH protocol were comparable with those that imply a treatment with 300 UI of rHuEpo. Key Words: Hemoglobin, hematocrit, reticulocytes, doping